Interrelation of the hammer swing technique with the technique of its previous rotation in highly skilled hammer throwers - Shesterova, L.; Rozhkov, V. (Slobozhanskyi herald of science and sport, 2018)
The results of studies on the relationship of the parameters of the hammer swing technique with the biomechanical indicators of the previous hammer rotation techniques are presented.